A Comprehensive Review of Physical Examination Tests of the Cervical Spine, Scapula, and Rotator Cuff. Issue 11 (1st June 2019) - Hippensteel, K. J.; Brophy, Robert; Smith, Matthew V.; Wright, Rick W.
Abstract : A thorough physical examination of the shoulder and cervical spine is critical in establishing a focused differential diagnosis of the pathology in and around the shoulder joint. Numerous tests have been described in the literature to help improve the diagnostic accuracy of specific shoulder or cervical spine pathology. A comprehensive approach for the physical examination of the cervical spine, scapula, and rotator cuff is presented and descriptions on how the tests are performed and the evidence behind why specific tests are used in enabling improved diagnosis of shoulder pathology are discussed.